2021
DOI: 10.3390/ma14154217
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Aspects, Optimization and Analysis of Cu-B-CrC Composites Fabricated by Powder Metallurgy

Abstract: Tribological properties of engineering components are a key issue due to their effect on the operational performance factors such as wear, surface characteristics, service life and in situ behavior. Thus, for better component quality, process parameters have major importance, especially for metal matrix composites (MMCs), which are a special class of materials used in a wide range of engineering applications including but not limited to structural, automotive and aeronautics. This paper deals with the tribolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 73 publications
2
24
0
Order By: Relevance
“…Moreover, it is a promising technique for tribological aspects which have been applied by researchers recently [ 26 , 27 ]. In this context, Taguchi-based DOE methodology was employed in this wear study.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it is a promising technique for tribological aspects which have been applied by researchers recently [ 26 , 27 ]. In this context, Taguchi-based DOE methodology was employed in this wear study.…”
Section: Methodsmentioning
confidence: 99%
“…They reported that the Gr particles reduced the hardness, while adding SiC increased it. Usca et al [39], created composite materials by combining B-CrC hybrid reinforcements in various ratios (0-2.5-5-7.5 wt.%) with copper. They discovered that increasing the reinforcement ratios resulted in an increase in hardness.…”
Section: Hardness Analysismentioning
confidence: 99%
“…As is known, the Taguchi approach uses objective functions in order to optimize the related response parameter. For this, three equations are used, namely maximization, minimization, and normalization equations [34][35][36]. Since the power, temperature, and wear parameters should ideally be minimal, the second equation is used.…”
Section: Experimental Design Optimization Approach and Statistical Analysismentioning
confidence: 99%